Disability, distress and unemployment in neurology outpatients with symptoms 'unexplained by organic disease'. Issue 7 (21st January 2011) - Carson, A; Stone, J; Hibberd, C; Murray, G; Duncan, R; Coleman, R; Warlow, C; Roberts, R; Pelosi, A; Cavanagh, J; Matthews, K; Goldbeck, R; et al.
Abstract : Objectives: To determine the disability, distress and employment status of new neurology outpatients with physical symptoms unexplained by organic disease and to compare them with patients with symptoms explained by organic disease. Methods: As part of a cohort study (the Scottish Neurological Symptoms Study) neurologists rated the extent to which each new patient's symptoms were explained by organic disease. Patients whose symptoms were rated as 'not at all' or only 'somewhat' explained by disease were considered cases, and those whose symptoms were 'largely' or 'completely' explained by disease were considered controls. All patients completed self-ratings of disability, health status (Medical Outcomes Study Short Form 12-Item Scale (SF-12)) and emotional distress (Hospital Anxiety and Depression Scale) and also reported their employment and state financial benefit status. Results: 3781 patients were recruited: 1144 (30%) cases and 2637 (70%) controls. Cases had worse physical health status (SF-12 score 42 vs 44; difference in means 1.7 (95% CI –2.5 to 0.9)) and worse mental health status (SF-12 score 43 vs 47; difference in means –3.5 (95% CI –4.3 to to 2.7)). Unemployment was similar in cases and controls (50% vs 50%) but cases were more likely not to be working for health reasons (54% vs 37% of the 50% not working; OR 2.0 (95% CI 1.6 to 2.4)) and also more likely to be receiving disability-related state financial benefits (27% vs 22%; (OR 1.3, 95% CI 1.1 to 1.6)). Conclusions: New neurology patients with symptoms unexplained by organic disease have more disability-, distress- and disability-related state financial benefits than patients with symptoms explained by disease.